2021
DOI: 10.1186/s40842-021-00120-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity for blood glucose control in gestational diabetes mellitus: rationale and recommendations for translational behavioral interventions

Abstract: Gestational Diabetes Mellitus (GDM) is associated with adverse health outcomes during pregnancy and beyond. Previous randomized controlled trials of exercise interventions have demonstrated that exercise, conducted primarily during supervised sessions, improves maternal glycemic control in women with GDM. However, additional research is needed to develop physical activity interventions that are easily implemented in healthcare settings (e.g., recommendations and strategies to increase non-supervised physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Intervention studies to date have shown that early implementation of dietary and physical activity interventions (in the first trimester) may reduce the risk of GDM. At the same time, studies confirm that the diagnosis and treatment of GDM (by modulating diet, promoting physical activity and pharmacotherapy including insulin) may improve results in the mother and the child [ 10 , 11 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies to date have shown that early implementation of dietary and physical activity interventions (in the first trimester) may reduce the risk of GDM. At the same time, studies confirm that the diagnosis and treatment of GDM (by modulating diet, promoting physical activity and pharmacotherapy including insulin) may improve results in the mother and the child [ 10 , 11 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most exercise interventions are supervised exercise and well resourced; potentially being difficult to translate into the healthcare setting. Integration of health coaching and evidence based behavioural strategies (goal setting, monitor and feedback) has been suggested to provide the most appropriate tools for translation of this evidence into clinical practice 37. +Stay Active integrates these key principles and has a unique ability for the clinicians to interact with the user.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it appears that a GDM diagnosis alone does not motivate women to increase their PA levels [ 84 , 85 ]. In GDM, apart from reducing GWG, exercise is also tightly related to the glycemic control, with lower PA levels being associated with increased blood glucose concentrations [ 86 , 87 ]. In parallel, exercise can also reduce the need for insulin [ 88 ] by facilitating glucose uptake in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, very few participants opted for the combined diet and exercise interventions despite being supervised. Indeed, most of the studies on women with GDM have applied supervised exercise interventions and, according to Onaade, this information is difficult to translate into everyday clinical practice [ 87 ].…”
Section: Discussionmentioning
confidence: 99%